Government Recurrent Expenditure and Human Capital Development in Nigeria, 1990-2018: An ARDL Analysis - Festus Babarinde, Gbenga (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This study investigates the impact of government recurrent expenditure on human capital development in Nigeria for the period between 1990 and 2018. It aims to determine the impact of government recurrent expenditures on health, education, pensions and gratuities, human capital development based on ex-post facto research design. The data for the study were annualized time series data obtained from United Nations Development Programme’s Human Development Report and Central Bank of Nigeria’s Statistical Bulletin. Autoregressive distributed lag (ARDL) regression were employed in data analysis. It was found that a strong, positive and significant correlation exists between each of the independent variables (government recurrent expenditure on education (GEDU); government recurrent expenditure on health (GHEL); government recurrent expenditure on pension and gratuities (GPAG)) and the dependent variable (human capital development (HCD). However, there was no long run co-movement among the variables. Furthermore, the ARDL regression results indicate that GEDU has a significant and positive impact on HCD. While its lag both in the first and second years contributed positively to HCD though not significant. GHEL, however, has negative and statistically insignificant impact on HCD. Its first year lag also follows suit. GPAG has positive and significant impact on HCD. The study concludes that both GEDU and GPAG have positive and significant impact on HCD in Nigeria. However, an inverse though insignificant relationship was found, between HCD and GHEL. It is therefore recommended that investments in education should constitute one of the uppermost in the allocation of resources of the federal government of Nigeria. Similarly, welfare of the retirees should be given proportional and equitable consideration just like those in active service.